The Role of Whistleblowing in Moderate Factors Affecting Accounting Fraud Tendencies - Hari, Kurnia Krisna; Sabrina, Nina; Meratia, Meratia (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Nearly 46% of companies worldwide reported cases of economic crime fraud in the past two years. The average company reported losing 5-10% of revenue due to fraud, including accounting fraud. Specific Background: From 2016 to date, more than 120 cases of fraud have been recorded in Indonesian state-owned enterprises, one of which is accounting report fraud. Knowledge Gap: Although whistleblowing is important, its moderating role in increasing information asymmetry, integrity and suitability of financial compensation on the tendency of accounting fraud is still not widely used. Aims: This research is intended to examine link information asymmetry, integrity and suitability of financial compensation on the tendency of accounting fraud which is moderated by whistleblowing. Methods: The 37 state-owned enterprises, 13 companies passed the sampling criteria and employees as financial managers, financial staff, accounting managers, and accounting staff were sampled. Data collection used questionnaires and interviews. The analysis technique used multiple linear regression and moderated regression analysis. Results: Whistleblowing strengthens the interaction relationship between information asymmetry and the tendency for accounting fraud and weakens the interaction relationship between integrity and the tendency for accounting fraud. Novelty: This study introduces whistleblowing as a moderating variable, which offers a new perspective on the tendency of accounting fraud in state-owned enterprises. Implications: This study explores the importance of whistleblowing systems in business activities. Information asymmetry and integrity has an influence on the tendenci for accounting fraud suggesting that such disclosure can enhance public trust.